Ambientes Virtuais para Educação a Distância: uma estrutura de classificação e análise de casos - Tathyane Dutra Cabral e Rosa Maria Esteves M. da Costa, Daniele Guimarães Alves (Cadernos do IME - Série Informática, 2013)
This work traces a profile related to virtual reality in distance education and conceptualizes a research framework to aid the study, design and development of virtual reality applications in distance curses. Some examples are classified in this framework and their common characteristics are discussed.